2007
DOI: 10.1213/01.ane.0000261508.24083.6c
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Isoflurane, Halothane and Pentobarbital on Noise-Induced Hearing Loss in Mice

Abstract: These findings indicate that, while halothane, isoflurane and pentobarbital could protect mice against NIHL and hair cell damage, inhaled anesthetics were more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…Isoflurane could thereby provide a neuroprotective effect, preventing damage to hair cells (as shown by Kim et al, 2005) or central auditory neurons. Since the neuroprotective effect of isoflurane reduces noise-induced hearing loss (Kim et al, 2005;Chung et al, 2007), this mechanism could directly explain the prevention of temporary tinnitus that we observed. Although we demonstrated that hearing loss at 6 kHz is unlikely to account for the gap-detection deficits that we used to measure tinnitus, it is still likely that the temporary tinnitus was caused by noise-induced hearing loss at higher frequencies.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Isoflurane could thereby provide a neuroprotective effect, preventing damage to hair cells (as shown by Kim et al, 2005) or central auditory neurons. Since the neuroprotective effect of isoflurane reduces noise-induced hearing loss (Kim et al, 2005;Chung et al, 2007), this mechanism could directly explain the prevention of temporary tinnitus that we observed. Although we demonstrated that hearing loss at 6 kHz is unlikely to account for the gap-detection deficits that we used to measure tinnitus, it is still likely that the temporary tinnitus was caused by noise-induced hearing loss at higher frequencies.…”
Section: Discussionmentioning
confidence: 68%
“…For experimental design of tinnitus studies, the use of anesthesia during noise exposure must be taken into careful consideration. While we used isoflurane because of the need for rapid recovery in our paradigm, other anesthetics such as pentobarbital have also been shown to reduce noise-induced hearing loss in mice (Chung et al, 2007) and might therefore show preventative effects on tinnitus similar to isoflurane. However, it is probably not necessary to conclude that anesthesia should never be used during noise exposure in tinnitus studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were exposed to 106-dB octave-band (8–16 kHz) white noise for 60 minutes in a custom-built, calibrated, reverberant sound chamber. Animals were unanesthetized in order to avoid affects of general anesthesia on sound-induced threshold shifts [27]. Click ABR thresholds were measured again at 1, 3, 7, and 18 days after noise exposure.…”
Section: Methodsmentioning
confidence: 99%
“…However, isoflurane has been shown to diminish the amplitude and duration of temporary tinnitus after a short exposure to loud sounds [25]. Under pentobarbital, isoflurane, or halothane anesthesia noise-induced hearing loss in mice is less (62.5 dB, 45.5 dB, 39.3 dB threshold increase, respectively) compared to the unanesthetized control group (77.5 dB threshold increase) [115]. In addition, the influence of anesthesia on any electrophysiological recordings has to be taken into account, as anesthesia influences the receptive fields and the spontaneous activity of the rat auditory cortex [116].…”
Section: Established Ways Of Tinnitus Induction In Animal Researchmentioning
confidence: 99%